2023
DOI: 10.3390/ijms241210247
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Identification of Genetic Alterations in Head and Neck Squamous Cell Carcinoma and Therapeutic Efficacy of HNC018 as a Novel Multi-Target Agent for c-MET/STAT3/AKT Signaling Axis

Abstract: Amongst the most prevalent malignancies worldwide, head and neck squamous cell carcinoma (HNSCC) is characterized by high morbidity and mortality. The failure of standard treatment modalities, such as surgery, radiotherapy, and chemotherapy, demands the need for in-depth understanding of the complex signaling networks involved in the development of treatment resistance. A tumor’s invasive growth and high levels of intrinsic or acquired treatment resistance are the primary causes of treatment failure. This may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Another recent study by Khedkar et al identified that higher expressions of MET, STAT3, and AKT were connected with poor overall survival in HNSCC patients, so they synthesized a small molecule HNC018 that targets these molecules. HNC018 decreased sphere formation and also increased the response to cisplatin and suppressed tumor growth in vivo [141]. Another study investigating MET as a CSC therapeutic target showed that MET inhibition induces the radiosensitization of HNSCC [142].…”
Section: Targeting Other Stem Cell Markersmentioning
confidence: 98%
“…Another recent study by Khedkar et al identified that higher expressions of MET, STAT3, and AKT were connected with poor overall survival in HNSCC patients, so they synthesized a small molecule HNC018 that targets these molecules. HNC018 decreased sphere formation and also increased the response to cisplatin and suppressed tumor growth in vivo [141]. Another study investigating MET as a CSC therapeutic target showed that MET inhibition induces the radiosensitization of HNSCC [142].…”
Section: Targeting Other Stem Cell Markersmentioning
confidence: 98%
“…The MET gene is overexpressed in over 75% of HNSCC and has an increased copy number of 13%, associated with tumor progression and tumor dissemination in the early stages ( 116 ). Mutations of the MET gene are reported less frequently, but they seem to be involved in lymph node metastasis ( 117 , 118 ). HNC may also carry somatic mutations in PIK3R1 (~7%) and PTEN genes ( 51 , 119 ), with loss of function in approximately 30% of HNC (more common than other cancers) due to mutations, loss of heterozygosity in the 10q region (which includes PTEN), detected in more than 70% of HNSCC, or hypermethylation, reported in ∼5% of these.…”
Section: Hnc Molecular Pathogenesismentioning
confidence: 99%